New Approaches for Effective Microwave Assisted Extraction of Caffeine and Catechins from Green Tea - Gönül SERDAR; Ezgi DEMİR; Serhat BAYRAK; Münevver SÖKMEN (International Journal of Secondary Metabolite)
This study was designed to develop an effective microwave assisted extraction (MAE) method for extraction of caffeine and catechins from green tea samples. A series of solvents (water, ethanol:water mixture or citric acid:water mixture) were used for extraction of green tea samples (fresh, frozen or dried) collected in three collection periods (first, second and third collection periods). Tea samples were extracted using water in a close microwave system under the certain extraction conditions. Extraction was carried out under a controlled 600 W microwave power at 80 oC temperature for 4 min irradiation time. Alternative to water, an ethanol-water mixture (1:1) or a citric acid-water (1:1) mixture was used as extracting solvent under the same conditions. After MAE crude aqueous extract was partitioned first with chloroform to separate caffeine then ethyl acetate for catechins. Both caffeine and catechin extraction was quite successful with microwave assisted system employing only 4 minutes treatment. The highest caffeine yield was obtained in the second collection period using frozen green tea samples and ethanol-water as extracting solvent. The yield of catechin extracts was between 0.84-3.96% depending on the solvent system used for extraction. Ethanol-water mixture seems to be appropriate for effective extraction in the basis of extract yields. However, HPLC results showed that individual catechin content of each extraction is more important criteria for the evaluation of most effective extraction medium rather than the mass of the extract. Using citric acid as extracting solvent in MAE seem to be more fruitful providing 100% catechin mixture with the highest EGCG content.